Reaksi Pasar Setelah Hasil Pemilu 2004 (Studi Terpilihnya SBY sebagai Presiden RI Periode 2004-2009) - Munari, Munari (Jurnal Riset Ekonomi dan Bisnis, 2007)
Interconnected political event sliver with economics stability a state. Chosen event  of Susilo Bambang Yudhoyono on 20 October 2004 representing political event  have national scale able to influence sentiment reaction of capital market in Indonesia is. Chosen of President of Susilo Bambang Yudhoyono on 20 October 2004 representing big achievement in democratian of Indonesian nation, namely Indonesian nation will execute election of president directly and in moderation if the event registered in general election history since Indonesia independence, because this matter represent firstly  times rill in democracy in Indonesia. Many economic observer of prediction that perpetrator of money market and stock market will react positive to the is chosen of Susilo Bambang Yudhoyono as President of RI, and also the nun  election at ease and peaceful relative. Based on breakdown of above hence this research aim to know and analyze abnormal difference  return and also stock  transaction volume before and after chosen event  of Susilo Bambang Yudhoyono on 20 October 2004.Object in this research manufacturing business which commerce of its active share  stock and joined into company of LQ- 45 on 20 October 2004 that is amounting to 16 company. To test hypothesis which  raised in this research hence used different test analysis technique one sample ( test t sample one) . Of analysis above data which have been showed that first hypothesis which raised namely there abnormal difference  return before and after chosen event of Susilo Bambang Yudhoyono on 20 October 2004, cannot be proven  its truth, the mentioned supported by result of examination with test of t where obtained  t-test equal to 0,763 with level of significant 0,465. and so do  second  hypothesis which raised namely there is difference  of volume trading of activity before and after chosen event  of Susilo Bambang Yudhoyono on 20 October 2004, cannot be proven  its truth, the mentioned supported by result of examination with test of t where obtained  t-test equal to 2,212 with level of signifikan 0,054. Keywords: Abnormal Return, Trading Volume Activity